Mg,Sr-Cosubstituted Hydroxyapatite with Improved Structural Properties - Elena Landi; Stefano Guizzardi; Elettra Papa; Carlo Galli (Applied Sciences, 2021)
Bone substitute materials require specific properties to make them suitable for implantation, such as biocompatibility and resistance to mechanical loads. Mg,Sr-cosubstituted hydroxyapatite (MgSr-HA) is a promising bone scaffold candidate because its structure is similar to the native bone matrix. However, MgSr-HA materials do not typically withstand thermal treatments over 800 °C, because Mg promotes HA degradation to less stable tricalcium phosphate, a compound that, albeit biocompatible, is not found in bone. We, therefore, designed an ion-exchange process to enrich sintered Sr-HA with Mg and obtain MgSr-HA porous constructs. These materials contained a 0.04–0.08 Mg/Ca molar ratio and a 0.12–0.13 Sr/Ca molar ratio, and had up to 20 MPa of compressive strength, suitable for use as bone fillers or scaffolds. Unlike previous synthetic Mg,Sr-substituted apatite powders, the proposed process did not degrade HA and thus preserved its similarity to bone structure. The obtained material thus combines the presence of bioactive Mg and Sr ions in the HA lattice with a 3D morphological/structural organization that can be customized in pore size and distribution, as well as in mechanical strength, thus potentially covering a wide range of clinical applications.